Interpretations about emphyteutic census redemption in Guatemala in late Nineteenth Century. The cases of Antigua Guatemala, San Felipe and San Mateo Milpas Altas - Ávila Quijas, Aquiles Omar (Centro de Historia Argentina y Americana, 2013)
This article analyses the interpretation that three city councils from the Department of Sacatepéquez, Guatemala (Antigua Guatemala, San Felipe and San Mateo Milpas Altas) made of the emphyteutic census redemption decree from 1877. The objective is to demonstrate that the signification of private property was related to the community-authority relationship and the social cohesion derived from it, which gives the opportunity to question the historiographical hypothesis that underline that indigenous city councils were impoverished and their land stripped during the Liberal Regime. To accomplish this there are traced to analysis ways, the first one is about community and the second one is drawn through collective action and institutionalism. Finally, it can be seen that the non-indigenous city council, Antigua Guatemala, was impoverished sooner, while the other two maintained their social dynamic and the money flow even when their lands were privatize.